Functional differences in emotion processing during adolescence and early adulthood - Vink, Matthijs; Derks, Jolanda M.; Hoogendam, Janna Marie; Hillegers, Manon; Kahn, René S. (NeuroImage (Orlando, Fla.), 2014)
Adolescence is a transitional period between childhood and adulthood and is characterized by emotional instability. Underlying this behavior may be an imbalance between the limbic subcortical areas and the prefrontal cortex. Here, we investigated differences in these regions during adolescence and young adulthood. Fifty subjects aged 10 to 24 viewed and rated neutral, negative, and positive pictures (IAPS: International Affective Picture System), while being scanned with functional MRI. Only those trials in which there was a match between the subject's response and the IAPS rating were included in the analyses. Task performance (matching accuracy, reaction times) did not differ across age. Activity in the amygdala and hippocampus decreased with age when processing emotional salient stimuli versus neutral stimuli. In contrast, activation in the ventrolateral prefrontal cortex increased with age. Importantly, we show for the first time that these age-related changes are paralleled by an increase in functional coupling of the amygdala and hippocampus with the orbitofrontal cortex and ventrolateral prefrontal cortex. These findings are in line with the general notion that brain development from childhood to adulthood is characterized by a gradual increase in frontal control over subcortical regions. Understanding these developmental changes is important as these may underlie typical adolescent behavior. •We studied developmental changes in brain regions involved in emotion processing.•Cross-sectional fMRI study in a sample of 50 participants aged 10–24•Activation in amygdala and hippocampus decreased with age.•Activation in frontal regions increased with age.•Functional coupling of amygdala and hippocampus with frontal regions increased with age.